2020
DOI: 10.3390/bs10020056
|View full text |Cite
|
Sign up to set email alerts
|

Ethno-National Attitudes as Intercultural Competence Predictors in University Students: Gender Differences

Abstract: The search for predictors of intercultural competence (ICC) development is one of the important challenges of modern psychology in connection with globalization in all the spheres of modern life, including university education. The purpose of the present research is to show that the ethno-national attitudes (ENA), which Khukhlaev et al. consider as an individual’s predisposition to assess the nationality/ethnicity can determine the severity of ICC features in male and female university students. The sample inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In contrast to the current findings, previous studies have found that intercultural awareness could promote a better understanding of others, resulting in positive effects [ 91 , 92 ]. However, it could appear that within the current study, intercultural awareness might not directly cause negativity toward others but instead increase the focus and preference towards one’s own culture [ 93 , 94 ]. The DMIS argued that information about a particular culture is not sufficient to prepare individuals for intercultural communication.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast to the current findings, previous studies have found that intercultural awareness could promote a better understanding of others, resulting in positive effects [ 91 , 92 ]. However, it could appear that within the current study, intercultural awareness might not directly cause negativity toward others but instead increase the focus and preference towards one’s own culture [ 93 , 94 ]. The DMIS argued that information about a particular culture is not sufficient to prepare individuals for intercultural communication.…”
Section: Discussionmentioning
confidence: 90%
“…In the final version of the ISS, the total raw scores for each subscale can range from 0 to 80 points. This version of the questionnaire has been well tested on different samples of Russian university and school students in our previous research ( Gridunova et al 2017 ; Gridunova 2018 ; Novikova et al 2017 ; Novikova et al 2019 ; Novikova et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In Russian ICC studies based on the modified version of DMIS, it was shown that male university students are more inclined to absolutize intercultural differences, i.e., ethnocentrism ( Logashenko 2015 ; Gridunova 2018 ), but, in general, gender differences are not very significant ( Novikova et al 2020 ). In other Russian studies based on the model by Barrett ( 2018 ), it was revealed that “for women, the success of intercultural interaction depends on practical skills, self-education, the ability to listen and understand, readiness for cooperation, tolerance; and for men—from respect and responsibility, adaptability, knowledge and their critical reflection” ( Makhmutova et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is also important to determine the variables that affect these attitudes. Novikova et al (2020) suggest a complex study of different intercultural competency predictors, such as social and cultural contexts and experiences, social attitudes, personality traits, national and/or cultural origin, gender, and age. In this sense, we aim to broadly examine the variables that affect intercultural sensitivity and ethnocentrism levels in a certain group.…”
Section: Introductionmentioning
confidence: 99%